Feministische Studien (De Gruyter, 1992)
The periodical Feministische Studien (Feminist Studies) is one of the most important interdisciplinary forums for gender research and research on women in German-speaking countries. For the past 30 years, Feministische Studien has participated in debates within the world of research and in the public sphere.